1991
DOI: 10.1002/eji.1830210606
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant extracellular domain of the human interleukin 4 receptor inhibits the biological effects of interleukin 4 on T and B lymphocytes

Abstract: Human interleukin 4 (IL4) acts on various hematopoietic cell types through interaction with a specific cell surface receptor (IL4R), whose cDNA has been cloned. We have produced a cDNA encoding a soluble form of the extracellular domain of the human IL 4R (sIL4R) and describe here the capacity of sIL4R to antagonize the in vitro activities of IL4 on normal B and T lymphocytes. sIL4R inhibited IL4-induced proliferation of both phytohemagglutinin-preactivated peripheral blood mononuclear cells (PBMC) and anti-Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 34 publications
2
21
0
2
Order By: Relevance
“…Concentrations effecting half-maximal responses (EC 50 values) were reported to range from 0.5 to 200 pM (e.g. Garrone et al, 1991;Rigley et al, 1991;Kruse et al, 1992). The IL-4 activities are mediated by a receptor system for which up to now only a single protein has been identified.…”
mentioning
confidence: 99%
“…Concentrations effecting half-maximal responses (EC 50 values) were reported to range from 0.5 to 200 pM (e.g. Garrone et al, 1991;Rigley et al, 1991;Kruse et al, 1992). The IL-4 activities are mediated by a receptor system for which up to now only a single protein has been identified.…”
mentioning
confidence: 99%
“…An alternative splice deletion of exon 8 was also identified that results in a putative membrane-bound form of receptor lacking the intracellular signaling domain sequences. These alternative splice forms may all be involved in serving as IL9 antagonists, as is the case of other cytokine receptors (such as IL4 and IL5 receptors), although the binding affinity of these receptors is greatly reduced (37)(38)(39). 6 In addition to the splice variants described above, the abundant ⌬Q transcript was also identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant sIL–4R was shown to neutralize IL–4 in vitro [8, 9]and in vivo [10, 11]suggesting that sIL–4R is a potential antagonist to IL–4, IL–4–driven proliferation and IL–5 upregulation by CD45RA+ human T cells were completely inhibited by human, but not murine recombinant sIL–4R. Therefore, sIL–4R seems to be a candidate to inhibit IL–4 bioactivity in vivo in diseases associated with IL–4 overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in mice two different cDNAs originating from the same gene were observed, one coding for the cell surface and the other for the sIL–4R [7]. Recombinant forms of the sIL–4R neutralize IL–4 in vitro [8, 9]and in vivo [10, 11]suggesting that sIL–4R is an antagonist to IL–4. However, IL–4 complexed to murine sIL–4R was found to be protected from proteases resulting in a prolonged half–life [12], a fast dissociation rate [12]and enhanced IgE synthesis in vivo [13].…”
Section: Introductionmentioning
confidence: 99%